Partition of spiramycin in a recyclable aqueous two-phase system based on pH-responsive and thermosensitive polymers. (December 2020) - Zhang, Yan; Zhang, Hongzhou; He, Dong; Cao, Xuejun; Wan, Junfen
Graphical Abstract: Highlights: A recyclable aqueous two-phase system was constructed using PADB6.26 and EO30 PO70 . Water-binding ability of polymers was detected to study phase separation mechanism. Spiramycin was separated from fermentation broth. The recoveries of PADB6.26 and EO30 PO70 reached 92.39% and 98.76%, respectively. Abstract: Aqueous two-phase systems have been widely studied for the separation and recovery of bioproducts. In this study, the thermosensitive polymer EO30 PO70 and pH-responsive polymers (PADB4.66 and PADB6.26 ) were used to develop a recyclable aqueous two-phase system suitable for spiramycin partitioning. EO30 PO70 represents poly-(ethylene oxide-propylene oxide), where 30 and 70 indicate the proportions of ethylene oxide and propylene oxide, respectively. PADB4.66 and PADB6.26 represent poly-(acrylic acid-dimethylamine ethyl methacrylate-butyl methacrylate), where the numbers (4.66 and 6.26) in the subscripts indicate the isoelectric point of the polymers. The phase separation mechanism of ATPS was studied through low-field nuclear magnetic resonance (LF-NMR) and surface tension. Moreover, the parameters affecting spiramycin partitioning, such as system components and composition, pH, temperature, and type and concentration of additive salt, were investigated. The best partitioning conditions were determined using 4.70% PADB6.26 and 31.67% EO30 PO70 in the presence of 0.05 mol/L NaSCN at 35 °C and pH = 9.2. The highest partition coefficient of spiramycin from fermentation broth was 11.92, with an extraction recovery of 97.69%. In addition, phase-forming polymers PADB6.26 and EO30 PO70 could be recovered by regulating the pH or temperature, and their recoveries reached 92.39% and 98.76%, respectively.